Acute Cytomegalovirus Infection as a Rare Cause of Portal Vein Thrombosis with Small Bowel Infarction in an Immunocompetent Patient. Issue 1 (29th March 2017) - Vael, Arnout; Degryse, Hendrik; Bracke, Peter
Portal vein thrombosis (PVT) refers to thrombosis that develops in the trunk of the portal vein including its right and left intrahepatic branches and may even extend to the splenic or superior mesenteric veins. PVT due to Cytomegalovirus (CMV) infection is a rare complication, scarcely described in English literature. We present a case of a 58-year-old immunocompetent patient with PVT and small bowel ischemia.